Peran Ibu Single Parent Sebagai Kepala Keluarga Ditinjau Dari Hukum Islam (Studi Kasus Di Desa Pantai Cermin Kecamatan Tanjung Pura Kabupaten Langkat) - Rawinda Rani; Azhar (Journal Smart Law, 2025)
This study aims to analyze the role of single mothers as heads of families in Pantai Cermin Village, Tanjung Pura District, Langkat Regency, including the obstacles they face and the Islamic legal perspective on this role. The study used a descriptive qualitative approach through interviews, observations, and documentation studies with five informants from two single-parent families. Theresults show that single mothers carry out dual roles as breadwinners, decision-makers, household managers, and educators. The obstacles they face include economic constraints, time management difficulties, physical and mental exhaustion, and low social support. From an Islamic legal perspective, the role of mothers as heads of families in emergencies is permissible as long as it iscarried out responsibly and aimed at meeting the family's needs. Therefore, this study concludes that despite facing various challenges, single mothers can still carry out their roles effectively through perseverance, adaptability, and support from Islamic values that emphasize family welfare.